PERJUANGAN GAJAH MADA DALAM PERLUASAN WILAYAH KEKUASAAN MAJAPAHIT DI NUSANTARA TAHUN 1336-1364 - Lilih Rahmawati; Tontowi Tontowi; Wakidi Wakidi (FKIP UNIVERSITAS LAMPUNG, 2013)
Gajah Mada was a character who was instrumental in the expansion of Majapahit empire in thearchipelago. Formulation of the problem in this study, namely